Solidaridad antifascista francesa y Octubre de 1934 - Roberto Ceamanos Llorens (Cahiers de Civilisation Espagnole Contemporaine)
This article studies the solidarity displayed by French antifascism in favor of the revolutionary forces in October 1934. This study about the organizations that emerged to coordinate the movement analyzes the competition between communists and socialists to lead it, describes the wide spectrum of protests, thus as the response of the French authorities to Spanish pressure. All this from the analysis of different primary sources, especially the Archives of the border French departments for the conviction of the value of the information they provide, combined with the archive of Paris área. It was in these territories where the Spanish presence was more numerous and where the transit and temporary stay of the refugees and the solidarity organizations with the Spanish revolutionaries were more active.